Nanosized titanium dioxide saturable absorber for soliton mode-locked thulium-doped fiber laser - Ahmed, M. H. M.; Mohd Yusoff, N.; Che Abdullah, C. A.; Alresheedi, M. T.; Rosli, N. S.; Talib, Z. A.; Mahdi, M. A. (Elsevier, 2021)
We demonstrate the potential of nanosized titanium dioxide (TiO2) in forming ultrashort pulses using a ring cavity thulium-doped fiber laser. A TiO2 polymer composite was transferred onto a microfiber through a spin coating technique to act as a light-absorbing material, saturable absorber (SA). The nonlinear transmission characteristics of this TiO2-SA exhibited 3.8% modulation depth and 17 MW/cm2 saturation intensity at 1.92 µm wavelength. At 1587 mW pump power, the central wavelength, average output power, pulse duration, peak power, and pulse energy were 1925.6 nm, 126.8 mW, 1.5 ps, 6.45 kW, and 11 nJ, respectively. The fabricated TiO2-SA displayed a wide pump power range of fundamental mode-locking at 11.53 MHz without any sign of laser-induced damage threshold or pulse breaking effect. This work has shown the potential use of nanosized TiO2-SA for fabricating broadband nonlinear photonic devices.